Association of Risk Factors of Coronary Heart Diseases and Socio-demographic Characteristics of Civil Employees of Combined Military Hospital Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Risk factors are the most ruinous and mischievous ingredient to develop coronary heart diseases (CHD). Factors contributing to develop CHD and their associates are, therefore, of prime importance. It needs endless splurge to address the issue.Objectives: To identify the attributing risk factors and socio-demographic characteristics of coronary heart disease among civilian employees of Combined Military Hospital (CMH) Dhaka.Materials and Methods:  This observational study was conducted on 287 civil employees of CMH, Dhaka from September to December 2011. Data were collected by interview using questionnaire and check list which includes blood pressure measurement, anthropometric measurement and biochemical examinations.Results: Respondent’s age range was 23 to 59 years, educational level up to class VIII were 56.4 % and more than that were 36.6%, illiterate were 7%. Regarding income low, medium and high income group were 40.4%, 56.8% and 2.8% respectively. It was found that 68.6% had normal BP, 61.3% practices moderate exercise. Among the respondents 72.2% has got 1-5 risk factors of CHD. Risk factors (p